2015
DOI: 10.1016/j.genhosppsych.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial myopathy and comorbid major depressive disorder: effectiveness of dTMS on gait and mood symptoms

Abstract: dTMS may be an alternative antidepressant strategy in patients with MMs, provided that they are free from seizures. The mechanism of improvement of motor disturbance may relate to dorsolateral prefrontal cortex stimulation and improved executive function and needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
2
Order By: Relevance
“…Several studies reported that dTMS reduced anxiety in patients with comorbid depression [21,[36][37][38][39]. It is possible that dTMS acts indirectly on CUD by reducing anxiety, in addition to the drugs which were ineffective on their own for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that dTMS reduced anxiety in patients with comorbid depression [21,[36][37][38][39]. It is possible that dTMS acts indirectly on CUD by reducing anxiety, in addition to the drugs which were ineffective on their own for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…91 An anxiety disorder as a manifestation of a MID has been described in nsMIDs. 91 Psychosis has been reported in MELAS, 86 KSS, 92 POLG1-related disorders, 93 infantile onset spinocerebellar ataxia, 94 Leigh syndrome, 95 and nsMIDs. 96 Psychiatric abnormalities particularly occur in patients with MELAS, in which 50% of cases are affected.…”
Section: Psychiatric Abnormalitiesmentioning
confidence: 99%
“…32 Several cases of subjects with CPEO and other mitochondrial disorders and comorbid mood disorders have been recorded. 32 , 84 86 Similar homozygous (and to a smaller extent heterozygous) mutations cause motor symptoms in mice. 87 In addition to motor dysfunction, these mice exhibit age-dependent increase in the number of mtDNA deletions, specifically in brain and muscle, 87 providing a potential link between CPEO and psychiatric disorders.…”
Section: The Comorbidity Of Psychiatric and Mitochondrial Disordersmentioning
confidence: 99%